A system for assessment of climatic air pollution levels in Bulgaria: description and first steps towards validation. (1st January 2011) - Syrakov, Dimiter; Spiridonov, Valery; Prodanova, Maria; Bogatchev, Andrey; Miloshev, Nikolai; Ganev, Kostadin; Katragkou, Eleni; Melas, Dimitrios; Poupkou, Anastasia; Markakis, Kostas; San Jose, Roberto; Luiz Pérez, Juan
The EC FP6 project CECILIA (http://www.cecilia-eu.org ) aims at climate change impacts and vulnerability assessment in targeted areas of Central and Eastern Europe. Emphasis is given to regional climate change modeling at resolution of 10 km. The respective weather patterns influence local air quality. For its assessment EPA Models-3 (MM5, CMAQ, SMOKE) is used. The meteorological input is produced by the climatic version of ALADIN weather forecast system. TNO emission inventory for 2000 is exploited. The boundary conditions are extracted from 50-km runs over Europe made in Aristotle University of Thessaloniki, Greece. Calculations for the period 1991–2000 are performed, results presented.